Income and policy choices: Evidence from parliamentary decisions and referenda - Marco Portmann; David Stadelmann; Reiner Eichenberger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyze political representation of preferences of different income groups by matching referendum outcomes for low, middle, and high-income voters with individual legislators decisions on identical policy proposals. Results indicate that legislators more closely represent preferences of rich voters than preferences of middle-income and poor voters, and legislators are more responsive towards the rich. Preferences of low, middle, and high-income voters are, however, correlated. Representation of income groups varies according to legislators party affiliations.
Keywords: D72; H30; D63; 330